2009
DOI: 10.1016/j.diff.2009.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A two-step strategy for neuronal differentiation in vitro of human dental follicle cells

Abstract: Human dental follicle cells (DFCs) derived from wisdom teeth are precursor cells for cementoblasts. In this study, we recognized that naïve DFCs express constitutively the early neural cell marker b-IIItubulin. Interestingly, DFCs formed b-III-tubulin-positive neurosphere-like cell clusters (NLCCs) on lowattachment cell culture dishes in serum-replacement medium (SRM). For a detailed examination of the neural differentiation potential, DFCs were cultivated in different compositions of SRM containing supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
53
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 29 publications
1
53
0
1
Order By: Relevance
“…54 It has also been known that DFSCs are derived from immature dental tissue of wisdom teeth and also possess this multilineage differentiation capacity. 55 It has been reported by the Morszeck group that DFSCs can form neurosphere-like structures when plated onto low-attachment cell culture dishes in serum-free medium containing EGF and FGF-2. They also discovered that DFSC-derived neural cells grown on laminin and gelatin display a relatively long axon-like cell extension, indicating that neural cell morphology and axonlike cell extensions were dependent on cell culture substrates.…”
Section: Neural Differentiation Of Dental Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 It has also been known that DFSCs are derived from immature dental tissue of wisdom teeth and also possess this multilineage differentiation capacity. 55 It has been reported by the Morszeck group that DFSCs can form neurosphere-like structures when plated onto low-attachment cell culture dishes in serum-free medium containing EGF and FGF-2. They also discovered that DFSC-derived neural cells grown on laminin and gelatin display a relatively long axon-like cell extension, indicating that neural cell morphology and axonlike cell extensions were dependent on cell culture substrates.…”
Section: Neural Differentiation Of Dental Stem Cellsmentioning
confidence: 99%
“…Also, they reported that the neuronal cell lineage differentiation into dopaminergic or GABAergic neurons was dependent on the time-dependent addition of neural stem cell supplements, such as EGF, FGF-2, and retinoic acid. 55 In addition to studies on the in vitro differentiation of dental stem cells into neural cells, there have been attempts to improve and regenerate nerve tissue via cell transplantation. One recent study demonstrated that implanted DPSCs support host axon guidance within a receptive host nervous system by secreting neurotrophic factors.…”
Section: Neural Differentiation Of Dental Stem Cellsmentioning
confidence: 99%
“…Recent studies have shown that Sema 7A and its receptors regulate osteoblast and osteoclast differentiation, both important for bone homeostasis 17,18) . The dental follicle is an ectomesenchymally derived connective tissue surrounding the tooth germ that contains stem cells and/or progenitor cells 19) Human dental follicle cells (hDFCs) also have the capacity to commit to multiple cell types, not only to cells of the osteoblastic lineage, but also to cells of adipogenic and neurogenic lineages 20,21) . We previously reported that hDFCs can differentiate into osteogenic lineage cells in osteogenic induction medium (OIM) without dexamethasone (DEX) 22,23) , which has various biological effects, including anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…This tissue contains stem cells and lineagecommitted progenitor cells or precursor cells of osteoblasts/ cementoblasts. hDFC also have the capacity to form various types of cells, not only of the osteoblastic/cementoblastic lineage 1,8) , but also of the adipogenic and neurogenic lineages 2,9) , when they receive appropriate signals. hDFC can be very easily obtained because they are exposed in several surgical operations such as extraction of impacted teeth.…”
Section: Introductionmentioning
confidence: 99%